The Effectiveness Of Personal Hospitality Attitude Regulations Assisted by Digital Pocket Books in Increasing The Brand Identity Of The Tourism Department - Aprilia, Lu'luwatin Rosdiana; Annishia, Fristi Bellia; Anggraeni Stj, Rr Christiana Mayang; Marini, Sri (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2024)
The study aims to evaluate the effectiveness of a Digital Pocketbook assisted by Personal Hospitality Attitude regulations to enhance the brand identity of the Tourism Department. This type of research is pre-experimental type One Group Pretest-Posttest Design. The Sample is students from the Tourism Department and outside the Tourism Department of Polimedia Kreatif, namely 30 people from the Tourism Department while 26 people came from non-tourism with the simple random sampling. Data analysis in this research is using hypothesis testing with paired sample t-test and to determine its effectiveness using the N-Gain test to determine effectiveness. The results are that respondents' pretest scores for both tourism and non-tourism obtained an average of 69.1. After being treated with personal hospitality attitude regulations with the help of a digital pocket book, respondents' posttest scores obtained an average of 87.3. Calculation results using SPSS 26 with the Paired Sample t-formula test, the researcher concluded that a significance value of 0.000 or meaning 0.000 < 0.05 was obtained, so Ho was rejected and Ha was accepted, and with the results of the hypothesis test or tcount = 8.066 > ttable = 2.045 and tcount = 12,478 > ttable = 2.060 which means Ho rejected and Ha accepted. Based on the results of the N-gain test obtained an average of 56.3% which is quite effective, as well as for non-Tourism major students the average was 57.38% which in categories are quite effective too. So, it can be concluded that the Personal Hospitality Attitude regulations assisted by digital pocketbooks are quite effective in increasing the brand identity of the tourism department in Polimedia Kreatif.